2001
DOI: 10.1557/jmr.2001.0275
|View full text |Cite
|
Sign up to set email alerts
|

Structure of heat-treated sol-gel SiO2 glasses containing silver

Abstract: The crystallization of bulk amorphous SiO 2 samples, prepared by the sol-gel method, was obtained by heat treatments in air at temperatures as low as 500°C. This occurs when silver is added to the precursor solutions in an amount such that it forms aggregates embedded in the glass. Another requirement to observe the low-temperature glass crystallization is that the bulk samples must be prepared from precursor solutions with specific compositions. These compositions, have a high H 2 O/TEOS ratio, which produces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 26 publications
3
21
0
Order By: Relevance
“…1 and 2, a more pronounced effect in the case of the samples A was observed. This crystallization process can be understood in accordance with the previous report [9,10,11] in two important aspects, a) it is the structure of the SiO 2 matrix which is determined by the relation H 2 O/TEOS in the starting solution. b) Due to diffusion process of the Ag atoms in the growth and nucleation of Ag colloidal particles.…”
Section: Discussion Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…1 and 2, a more pronounced effect in the case of the samples A was observed. This crystallization process can be understood in accordance with the previous report [9,10,11] in two important aspects, a) it is the structure of the SiO 2 matrix which is determined by the relation H 2 O/TEOS in the starting solution. b) Due to diffusion process of the Ag atoms in the growth and nucleation of Ag colloidal particles.…”
Section: Discussion Resultssupporting
confidence: 84%
“…In the same way recently our research group has reported the crystallization of SiO 2 sol-gel made with the introduction of the metal nitrates in the starting solution, Ag, Cu and mixtures of Ag and Cu [9,10,11,12] obtaining low temperatures of crystallization, 600 ºC for quartz in the mixture with AgNO 3 and (Cu(NO 3 ) 2 ) and 500 ºC for the α-cristobalite with the introduction of AgNO 3 .…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations